A micromechanical approach to the mechanical characterization of 3D-printed composites. (10th February 2022) - Sayyidmousavi, Alireza; Fawaz, Zouheir
Aiming for the development of experimentally validated computational models to predict the mechanical properties of 3D-printed composites, the present study proposes a micromechanical approach by using a simplified unit cell model to characterize the material properties and behavior of 3D-printed composites manufactured through fused deposition modeling. The effective properties of the voided polymer matrix phase of the material are computed by calculating the void density as a tensorial meso-structural variable. These effective properties along with those of the fiber are input into a simplified micromechanical model to predict the material properties of the 3D-printed composite. The predictions are seen to be in very good agreement with the experimental values. The present approach is much simpler and less computationally costly compared to the finite element homogenization method. In addition, the present approach has the potential to simulate the response of the 3D-printed composite under different loading conditions.